The Effectiveness of YouTube Video-Based Learning in Enhancing Vocabulary Development Among Vocational High School Students - Olivia Julianti; Sunarti; Yeni Rahmawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aimed to investigate the effectiveness of YouTube videos in improving vocabulary acquisition among vocational EFL students. A mixed-methods within-subject design was employed involving 32 third-year vocational students in Indonesia. Quantitative data were collected through pre-test and post-test vocabulary assessments and analyzed using paired-samples t-tests, while qualitative data were obtained from semi-structured interviews to explore students’ learning experiences. The results showed a significant improvement in students’ vocabulary achievement, with the mean score increasing from 56.84 (SD = 8.21) in the pre-test to 78.12 (SD = 7.65) in the post-test (p < .001), indicating a large effect size (Cohen’s d = 1.32). These findings confirm a substantial gain in vocabulary mastery after the integration of YouTube videos in instruction. Qualitative analysis revealed that YouTube-based learning enhanced students’ motivation and engagement through audiovisual input, contextualized examples, and varied learning materials. Students reported that visual support, pronunciation models, and repeated exposure helped them understand and retain new vocabulary more effectively. Nevertheless, several challenges were identified, including fast speech rates, occasional subtitle inaccuracies, and the need to verify vocabulary correctness. Overall, the study concludes that YouTube video-based learning is an effective instructional tool for supporting vocabulary development in vocational EFL contexts when supported by structured instructional design and appropriate teacher guidance.